The Influence of Social Media Marketing on Customer Satisfaction and Repurchase Intention on the Tiktok Shop Platform - Murdiana, Murdiana; Archie, Ananda (UNIVERSITAS PAKUAN, 2025)
The development of e-commerce and social media has brought significant changes in the way people shop, especially through platforms such as TikTok Shop. This study aims to analyze the influence of social media marketing on customer satisfaction and repurchase intention on TikTok Shop. Based on the survey, TikTok Shop has become a popular e-commerce platform in Indonesia. The type of research used in this study is associative, which aims to explore the relationship between social media marketing, customer satisfaction, and repurchase intention. The data in this study uses primary and secondary data. Primary data was collected through a questionnaire distributed to active TikTok Shop users in Pontianak, while secondary data includes respondents' use of social media for shopping. Data analysis techniques used Partial Least Squares (PLS) in Structural Equation Modeling (SEM). The results of the study indicate that social media marketing has a positive and significant effect on customer satisfaction. Additionally, customer satisfaction has a positive and significant effect on repurchase intention. Social media marketing also shows an indirect influence on repurchase intention through customer satisfaction. The coefficient of determination (R²) indicates that social media marketing and customer satisfaction together influence repurchase intention with a significant contribution. This study suggests that companies should focus more on social media-based digital marketing to improve customer satisfaction and encourage repurchase intention.